Differences in bioelectrical activity of quadriceps muscle during various types of contraction - Niespodzinski, B.; Lukowicz, M.; Mieszkowski, J. (Baltic Journal of Health and Physical Activity, 2013)
Background: The aim of the study was to estimate differences in bioelectrical activity between rectus femoris (RF) and vastus medialis (VM) muscles of each lower limb.